RISK FACTORS AND TREATMENT OF ACUTE KIDNEY INJURY - Zakon, K.; Kolesnyk, M. (Ukrainian Journal of Nephrology and Dialysis, 2017)
This is review of current state in epidemiology and risk factors of acute kidney injury (AKI). Classification, diagnosis and treatment also discussed as well as risk factors of death of patients with AKI.